Using attribution to foster public support for alternative policies to combat obesity. (12th February 2018) - Garbarino, Ellen; Henry, Paul; Kerfoot, Sally
Abstract : Purpose: An increasing array of policies have been suggested to combat rising obesity. Regardless of the policy intervention that is selected each comes with a cost in the form of imposition on the public purse, or regulative restrictions on business or individuals. Consequently, potential opposition makes it critical to garner sufficient public support for whichever policy is selected. The purpose of this paper is to explore the ability of attributional framing for the causes of obesity (framed around locus of control and controllability) to increase support for a range of policy interventions designed to reduce obesity. Design/methodology/approach: Using an online panel, the authors manipulate the perceived cause of obesity along the internal/external locus and controllability/uncontrollability dimensions to assess whether attribution of causes of obesity can influence support for policy interventions that either encourage positive behaviour or discourage negative behaviour. Findings: The authors find that framing the causes of obesity to emphasise internal/external locus and controllability/uncontrollability has significant and predictable effects on policy support for men but not for women. In this American study, they show that men are more open to persuasion because their views on the causes of obesity are less firmly held than women. Practical implications: Highlighting the external and controllable causes of obesity was the most effective, suggesting that emphasising the role of the food industry in obesity can garner public support amongst males for a broad range of policy types. The limited effectiveness with women suggests that media focus be directed at male-oriented channels and outlets. Originality/value: The authors show that, at least amongst men, attribution framing can be used as a tool to increase support for policy interventions to prevent obesity.